2008
DOI: 10.1038/ni.1605
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of lymphoid organ integrity through the interaction of lymphoid tissue–inducer cells with stroma of the T cell zone

Abstract: The generation of lymphoid microenvironments in early life depends on the interaction of lymphoid tissue-inducer cells with stromal lymphoid tissue-organizer cells. Whether this cellular interface stays operational in adult secondary lymphoid organs has remained elusive. We show here that during acute infection with lymphocytic choriomeningitis virus, antiviral cytotoxic T cells destroyed infected T cell zone stromal cells, which led to profound disruption of secondary lymphoid organ integrity. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
309
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(325 citation statements)
references
References 57 publications
8
309
4
2
Order By: Relevance
“…Within the splenic white pulp, there is also disruption to both the follicular DC (FDC) network in B cell follicles (21) and the gp38 + fibroblastic reticular cell (FRC) network that guides T cell and DC migration in the T cell zone (22). Similar alterations to splenic architecture are also observed in other infectious causes of splenomegaly, including experimental malaria (23,24), trypanosomiasis (25), and following infection with LCMV (26)(27)(28); furthermore, although less well characterized, they are also a feature of human VL (29).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Within the splenic white pulp, there is also disruption to both the follicular DC (FDC) network in B cell follicles (21) and the gp38 + fibroblastic reticular cell (FRC) network that guides T cell and DC migration in the T cell zone (22). Similar alterations to splenic architecture are also observed in other infectious causes of splenomegaly, including experimental malaria (23,24), trypanosomiasis (25), and following infection with LCMV (26)(27)(28); furthermore, although less well characterized, they are also a feature of human VL (29).…”
Section: Introductionmentioning
confidence: 58%
“…Thus, we and others have proposed that lymphoid tissue remodeling may be a common mechanism that underpins disease-associated immunosuppression (18,22,26,28). Direct evidence in support of this concept has recently been obtained in mice infected with LCMV.…”
Section: Introductionmentioning
confidence: 76%
“…IL‐22 production by ILC3s is critical in containing commensal bacteria,25 and IL‐23‐responsive ILC3s also mediate colitis26 and accumulate in the inflamed intestine of CD patients 27. ILC3s also include the LTi cells involved in organizing tertiary lymphoid structures and tissue repair 28, 29…”
Section: The Ilc Familymentioning
confidence: 99%
“…However, recent studies indicated that plasticity in LN structural organization continues to exist throughout life, particularly during inflammation and infection (8,9). Reorganization of LN microanatomy during inflammation is characterized by the remodeling and expansion of key LN stromal cells, including lymphatic endothelial cells (LECs) (10), blood endothelial cells (BECs) (11,12), and fibroblastic reticular cells (FRCs) (13,14). Importantly, increasing evidence reveal the immunological significance of the remodeling of these stromal elements.…”
mentioning
confidence: 99%